Hubungan Health Literacy dengan Pola Menyusui pada Ibu Nifas: The Relationship Between Health Literacy and Breastfeeding Patterns in Postpartum Mothers - Atikah Fatmawati; Ika Suhartanti; Diana Eka Rahmawati (Universitas Airlangga, 2023)
Background: Breast milk is the best food for babies because it contains complete nutrients, hygienic, and safe. Breastfeeding cannot be separated from the pattern of breastfeeding applied. One of the factors that determine the application of breastfeeding patterns to the mother according to the needs of the baby is Health Literacy (HL). Objectives: This study aimed to determine the relationship between health literacy and breastfeeding patterns in postpartum mothers at Lavalette Hospital, Malang. Methods: The type of research used was a cross sectional study. The research population was all postpartum mothers. The sampling technique used was quota sampling, with 30 respondents. Data was collected using the Short-Form Health Literacy Questionnaire (HLS-SF-12Q) and breastfeeding pattern questionnaires. The data was then analyzed using the Spearman-Rank test (α <0.05). Results: The study found that most respondents had HL (56.7%) and breastfeeding patterns (56.7%) in the good category. Based on the statistical test obtained p value = 0.012, there was a significant relationship between HL and breastfeeding patterns in postpartum mothers. The correlation coefficient value was obtained at 0.455, indicating that the strength of the relationship was moderate. Conclusions: By having a good HL, mothers can apply the right breastfeeding patterns, selecting the duration, frequency, and good position, so that it has a positive impact during the breastfeeding process. It also reduces the chance of exclusive breastfeeding failure. Health workers are advised to be more massive in providing education related to breastfeeding patterns and their application, as well as increasing HL wisely and positively.